Aging or chronic stress impairs working memory and modulates GABA and glutamate gene expression in prelimbic cortex - Gandy, Hannah M.; Hollis, Fiona; Hernandez, Caesar M.; McQuail, Joseph A. (Frontiers in Aging Neuroscience, 2024)
The glucocorticoid (GC) hypothesis posits that effects of stress and dysregulated hypothalamic-pituitary-adrenal axis activity accumulate over the lifespan and contribute to impairment of neural function and cognition in advanced aging. The validity of the GC hypothesis is bolstered by a wealth of studies that investigate aging of the hippocampus and decline of associated mnemonic functions. The prefrontal cortex (PFC) mediates working memory which also decreases with age. While the PFC is susceptible to stress and GCs, few studies have formally assessed the application of the GC hypothesis to PFC aging and working memory. Using parallel behavioral and molecular approaches, we compared the effects of normal aging versus chronic variable stress (CVS) on working memory and expression of genes that encode for effectors of glutamate and GABA signaling in male F344 rats. Using an operant delayed match-to-sample test of PFC-dependent working memory, we determined that normal aging and CVS each significantly impaired mnemonic accuracy and reduced the total number of completed trials. We then determined that normal aging increased expression of Slc6a11, which encodes for GAT-3 GABA transporter expressed by astrocytes, in the prelimbic (PrL) subregion of the PFC. CVS increased PrL expression of genes associated with glutamatergic synapses: Grin2b that encodes the GluN2B subunit of NMDA receptor, Grm4 that encodes for metabotropic glutamate receptor 4 (mGluR4), and Plcb1 that encodes for phospholipase C beta 1, an intracellular signaling enzyme that transduces signaling of Group I mGluRs. Beyond the identification of specific genes that were differentially expressed between the PrL in normal aging or CVS, examination of Log2 fold-changes for all expressed glutamate and GABA genes revealed a positive association between molecular phenotypes of aging and CVS in the PrL but no association in the infralimbic subregion. Consistent with predictions of the GC hypothesis, PFC-dependent working memory and PrL glutamate/GABA gene expression demonstrate comparable sensitivity to aging and chronic stress. However, changes in expression of specific genes affiliated with regulation of extracellular GABA in normal aging vs. genes encoding for effectors of glutamatergic signaling during CVS suggest the presence of unique manifestations of imbalanced inhibitory and excitatory signaling in the PFC.